GC-MS Analysis of The Compounds Produced from Two Species of Penicillium - Hawraa Al-abedi (Basrah Journal of Veterinary Research)
Penicillium is a genus of the one the most common fungi have located in distinctive and suitable surroundings (temperature, humidity, Ph), Penicillium species produced extracellular enzymes that play a necessary position in the microbial decomposition of natural substances. The study is aimed to detect chemicals made by two species of Penicillium using a synthetic media that contained a powder made from the leaves of the Conocarups tree. In this study, two species of Penicillium had used in a fermentation process using synthetic medium contained a powder of the Conocarpus tree leaves. That isolated from water of the Hammar marsh areas in south Iraq particularly in Thi-Qar province.The isolated Penicillium observed on beginning of cultural, microscopic and morphological characteristics. Molecular identification of Penicillium results proved that all strains were belonging to Penicillium genera. According to the β-tubulin sequence, the isolated were divided into 2 species, as Penicillium brevicompactum and Penicillium expansum. GC-MS analysis appeared different compounds with various retention times (RTs) were produced by the crude extracts of P. brevicompactum and P. expansum. Similar compounds are  (benzyl alcohol, benzyldimethylsilyl ether ), (cyclotetrasiloxane, octamethyl), (trolamine), (cyclooctasiloxane, hexadecamethyl-),  (methyl stearate), (hexadecanoic acid, methyl ester), (n-hexadecanoic acid ), (9-octadecenoic acid, methyl ester,(E-), (9-octadecenoic acid, methyl ester), (heptadecanoic acid, 16-methyl-, methyl ester), (methyl stearate), (9-octadecenoic acid, (E)-), (oleic acid), (methyl 10-trans,12-cis-octadecadienoate), (9,12-octadecadienoic acid (Z,Z)-,methyl ester), (dl-.alpha.-tocopherol), (vitamin E), (gamma.-sitosterol), and (beta.-sitosterol).